Applying active force control with fuzzy self-tuning PID to improve the performance of an antilock braking system - Mohammed Hussin Ahmed Al-Mola (Universiti Malaysia Perlis (UniMAP), 2022)
Link to publisher's homepage at http://ijneam.unimap.edu.my